Implementation Of The Principle Of Disclosure In Share Trading In Primary Market And Secondary Market - Budi Praptio (Institute Of computer Science (IOCS), 2020)
The capital market has an important role in a country. The principle of openness is a core issue in the capital market and is at the same time the soul of the capital market itself. The problems that will be discussed in writing this thesis are about what are the benefits and objectives of implementing the principle of openness in the primary and secondary markets, then discussed about how the regulation of stock trading is carried out in the primary market and secondary market, and finally discussed how the regulation of the principle of openness to share trading carried out in the primary and secondary markets. The research that will be conducted is normative legal research. Normative research based on primary and secondary legal materials, namely the intarization of regulations relating to the writing of the author's thesis. The data collection technique was carried out by means of library research (library research). From the data that has been collected, both primary data and secondary data, then processed and analyzed using qualitative descriptive analysis techniques. The principle of openness plays an important role in the trading process in the primary and secondary markets. Disclosure about material facts is the soul of the capital market based on the existence of the principle of openness that allows for the availability of consideration for investors, so that they can rationally make decisions to buy or sell shares. The legal basis governing this stock trading can be seen in Article 7 paragraph (1), Article 9 paragraph (1) and Article 95 of Law Number 8 of 1995 concerning the Capital Market. These articles regulate the provisions that must be implemented and must not be violated by capital market players in order to create orderly, fair and efficient securities trading. The regulation regarding the principle of openness in trade is regulated in Chapter X (Article 85-89) of Law Number 8 of 1995 concerning the Capital Market. The implementation of the principle of openness in stock trading in the primary market is centered in the delivery of information on share offerings through prospectuses. Meanwhile, openness in the secondary market is very dominant and crucial in determining stock prices.